A criação do sujeito comunicação, artista e obra em processo - Fernandes, Sylvia Ribeiro (2006)
This thesis intends to demonstrate that the artistic work and the creator are part of a communicational process. They are produced as from a language directed to the other and are signs to be interpreted, in constant circulation in the culture. The psychoanalysis theoretical reference, of freudian and Lacanian approach, is used, as well as operators of a theory of artistic creation of peircean semiotic basis, based in the studies of genetic criticism and process criticism. The relationship between the psychoanalysis and the artistic communication is fundamentally marked by the analysis of the unconscious implications in the content of the artistic works, in the creator and in the esthetical effect on the other. This thesis displaces the analysis from the work to the creative process and its relationship with the constitution of the subjectivity. The poetic projects of two contemporary Brazilian plastic artists, Norma Grinberg and Sergio Fingermann, are analyzed as from the communications made by the artists themselves on their creation process in texts in the printed media. What is shown is that these artists poetic project is built as from the desire marks, constituted by the language; it is also shown that the work and the subject are built in a processual and joint way, as from a permanent communication process which holds what is made language and the incommunicable